2017
DOI: 10.1128/aem.03472-16
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of a Functional Flavin Mononucleotide Prenyltransferase for the Activity of a Bacterial Decarboxylase in a Heterologous Muconic Acid Pathway in Saccharomyces cerevisiae

Abstract: Biotechnological production of cis,cis-muconic acid from renewable feedstocks is an environmentally sustainable alternative to conventional, petroleum-based methods. Even though a heterologous production pathway for cis,cis-muconic acid has already been established in the host organism Saccharomyces cerevisiae, the generation of industrially relevant amounts of cis,cis-muconic acid is hampered by the low activity of the bacterial protocatechuic acid (PCA) decarboxylase AroY isomeric subunit C iso (AroY-C iso )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
2
19
0
1
Order By: Relevance
“…Because PCA decarboxylase enzymes require the prenylated form of flavin mononucleotide (prFMN) cofactor for functionality, we postulated that an insufficient supply of this cofactor constrains AroY activity in yeast. Moreover, recent studies (6,24) have shown that CEN.PK family strains of S. cerevisiae do not produce functional Pad1, which is responsible for activation of the endogenous yeast Fdc1 decarboxylase, as well as some bacterial decarboxylases, including AroY (24). We hypothesized that introducing Pad1 from S. cerevisiae strain S288C into our engineered CEN.PK strains would activate AroY, thus triggering conversion of PCA to catechol and MA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because PCA decarboxylase enzymes require the prenylated form of flavin mononucleotide (prFMN) cofactor for functionality, we postulated that an insufficient supply of this cofactor constrains AroY activity in yeast. Moreover, recent studies (6,24) have shown that CEN.PK family strains of S. cerevisiae do not produce functional Pad1, which is responsible for activation of the endogenous yeast Fdc1 decarboxylase, as well as some bacterial decarboxylases, including AroY (24). We hypothesized that introducing Pad1 from S. cerevisiae strain S288C into our engineered CEN.PK strains would activate AroY, thus triggering conversion of PCA to catechol and MA.…”
Section: Resultsmentioning
confidence: 99%
“…Here we targeted the shikimate precursor DHS to serve as the basis for building a synthetic MA production strain. Engineered bioproduction of MA is not without precedent, as many recent reports have detailed the successful reconstitution of heterologous MA pathways in S. cerevisiae (4,8,(12)(13)(14)(15)(16)24). A major caveat of many of these approaches involves the generation of aromatic amino acid auxotrophy resulting from deleterious manipulation of the pentafunctional Aro1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…In all these engineered yeast strains, the PCA decarboxylase AroY seems to be the bottleneck step, causing significant accumulation of PCA and thus, low MA titers. Some studies have suggested that this is due to the O 2 sensitivity of this enzyme (Suastegui et al, 2016b;Weber et al, 2012), while others believe that its functionality requires the prenylated form of flavin mononucleotide as the cofactor, which is insufficient or even missing in some strains, such as the CEN.PK family of S. cerevisiae (Weber et al, 2017). Supplying the strain with an overexpressed flavin mononucleotide prenyltransferase (Pad1) addresses this bottleneck.…”
Section: Ciscis-muconic Acidmentioning
confidence: 99%
“…We constructed plasmids from which ARO7 fbr , PHA2 and hmaS from N. uniformis were expressed – either with or without a mitochondrial or a peroxisomal targeting sequence, MTS or ePTS1 , respectively (for codon-optimized sequences see Supplementary table S4 ). We chose the mitochondrial targeting sequence of N. crassa ATP synthase subunit 9, which was previously shown to efficiently localize proteins to the mitochondria of S. cerevisiae ( Benisch and Boles, 2014 , Weber et al, 2017 , Westermann and Neupert, 2000 ). For peroxisomal localization we chose the enhanced peroxisomal targeting sequence ePTS1 that was identified by DeLoache et al (2016) and shown to cause efficient protein relocation into peroxisomes.…”
Section: Resultsmentioning
confidence: 99%